Contrastive linguistics: Prospects and problems - Butler, J.B.
Contrastive linguistics is a practice-oriented linguistic approach that seeks to describe the differences and similarities between a pair of languages. Contrastive Linguistics, roughly defined as a subdiscipline of linguistics which is concerned with the comparison of two or more (subsystems of) languages, has long been associated primarily with language teaching. Apart from this applied aspect, however, it also has a strong theoretical purpose, contributing to our understanding of language typology and language universals. This book features the prospects and issues of contrastive linguistics. 3P 6051271031 Koyum Yurdum ve Almanya Koyum Yurdum ve Almanya 3P 5824317240 Rossiyskoe gosudarstvo ot istokov do XIX veka: territoriya i vlast This monograph studies the connections between territory and form of power at the Russian state as a vast Eurasian state. The authors analyze the historical sources on the character of Russian statehood and the reasons for territorial expansion in the 15th – 18th centuries. The authors also analyze the functions of the Russian state as shield" and "bridge" between Europe and Asia and its mission of "preserving the balance". The book offers its analysis of the following issues: the formation of the ideology of empire as a special type of state and the Russian doctrine of autocracy; extension of territory as a geopolitical factor of Russian statehood